Borescopes as a Training Tool for Neuroendoscopy - Bakhsh, Aman; Bajaj, Jitin; Yadav, Mansi; Patidar, Jayant; Ratre, Shailendra; Parihar, Vijay S.; Yadav, Yad R. (Indian Journal of Neurosurgery, 2024)
Background Neuroendoscopy is increasingly utilized as a minimally invasive method. Due to its challenging learning process, there is a pressing need for cost-efficient training methods for residents and fellows in these surgeries. One such modality is using borescopes as substitutes for endoscopes, which could prove beneficial in resource-limited settings. However, existing literature on the use of borescopes in surgical practice for training remains scarce.Methods A thorough literature review was conducted to assess the applicability of borescopes. The search encompassed original articles, review articles, and randomized control trials on PubMed and Cochrane library. Studies were analyzed to evaluate the operability and limitations of borescopes in medical settings, considering factors such as light source, water resistance, sterility, camera quality, rigidity, ease of operation, and cost. This review also draws on practical experience using borescopes in endoscopic training, supplemented by feedback from neuroendoscopic fellows and consultants who have participated in our biannual workshops since March 2022.Results The literature search yielded 522 articles, which, after applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, resulted in 61 studies meeting the inclusion criteria. Universal serial bus (USB) powered borescopes have been employed as substitutes for endoscopes in training models using practice models and cadavers, facilitating the study of neuroanatomy and aiding in airway visualization during laryngoscopy. Despite lower resolution and fidelity compared to traditional endoscopy towers, their versatility and enhanced functionality through attachments make them an affordable alternative for endoscopes, contributing to improved surgical proficiency.Conclusion Borescopes have demonstrated potential as substitutes for endoscopes in training models, with positive feedback from trial participants suggesting broader applications in practice settings and possibly even clinics. This could ultimately enhance accessibility to endoscopic surgery, particularly in underserved regions.
Keywords: borescope; endoscope; neuroendoscopy; skill training; surgical practice